Fixation of carbon dioxide by chemoautotrophic bacteria in grassland soil under dark conditions. (19th May 2017) - Yang, Jun; Kang, Yumei; Sakurai, Katsutoshi; Ohnishi, Kouhei
ABSTRACT: Grassland is one of the most important terrestrial ecosystems for carbon (C) and nitrogen (N) cycling. However, while CO2 fixation by phototrophic bacteria is relatively well studied, little is known about microbial CO2 fixation without light by chemoautotrophic bacteria in grassland soils. Therefore, in this study, the isotope 14 C-CO2 was used to investigate the CO2 -fixing process in grassland soils. Soil samples were collected from both fenced and adjacent continuous grazing grassland sites in Inner Mongolia and then incubated for 120 days under dark conditions. Meanwhile, the cbbL genes (red- and green-like) were analyzed to isolate chemoautotrophic bacteria, which are responsible for CO2 fixation. After incubation, 14 C was fixed into soil organic carbon ( 14 C-SOC) and microbial biomass carbon ( 14 C-MBC) were found in both the fenced and grazing soils, and the fixation rate of 14 C-SOC in the fenced soils (48.55‰) was significantly higher than in the grazing soils (22.11‰). The fixation rate of 14 C-MBC in the fenced soils (14.05‰) was higher than in the grazing soils (7.08‰), but the difference was not significant. The red-like cbbL genes could be detected in all the soil samples, but the green-like cbbL genes could not be amplified. A greater number of identified operational taxonomic units were observed in the fenced soils compared with the grazing soils. The chemoautotrophic bacteria were mainly affiliated with Alphaproteobacteria and Actinobacteria. However, Chloroflexi was detected in only the fenced soils. The results suggested that CO2 fixation by chemoautotrophic bacteria might be significant in carbon cycling in grassland.